Differences in aquatic respiration in two contrasting streams: forested vs. agricultural - Dorley, Jancoba; Singley, Joel; Covino, Tim; Singha, Kamini; Gooseff, Michael N.; González-Pinzón, Ricardo (Frontiers in Water, 2024)
Land cover changes alter hydrologic (e.g., infiltration-runoff), biochemical (e.g., nutrient loads), and ecological processes (e.g., stream metabolism). We quantified differences in aquatic ecosystem respiration in two contrasting stream reaches from a forested watershed in Colorado (1st-order reach) and an agricultural watershed in Iowa (3rd-order reach). We conducted two rounds of experiments in each of these reaches, featuring four sets of continuous injections of Cl− as a conservative tracer, resazurin as a proxy for aerobic respiration, and one of the following nutrient treatments: (a) N, (b) N + C, (c) N + P, and (d) C + N + P. With those methods providing consistent information about solute transport, stream respiration, and nutrient processing at the same spatiotemporal scales, we sought to address: (1) Are respiration rates correlated with conservative transport metrics in forested or agricultural streams? and (2) Can short-term modifications of stoichiometric conditions (C:N:P ratios) override respiration patterns, or do long-term physicochemical conditions control those patterns? We found greater respiration in the reach located in the forested watershed but no correlations between respiration, discharge, and advective or transient storage timescales. All the experiments conducted in the agricultural stream featured a reaction-limited transformation of resazurin, suggesting the existence of nutrient or carbon limitations on respiration that our short-term nutrient treatments did not remove. In contrast, the forested stream was characterized by nearly balanced transformation and transient storage timescales. We also found that our short-lived nutrient treatments had minimal influence on the significantly different respiration patterns observed between reaches, which are most likely driven by the longer-term and highly contrasting ambient nutrient concentrations at each site. Our experimental results agree with large-scale analyses suggesting greater microbial respiration in headwater streams in the U.S. Western Mountains region than in second-to-third-order streams in the U.S. Temperate Plains region.